A rare case of a retroperitoneal cystic lymphangioma - Janugade, Hemant B.; Chhabra, Raunaq S.; Janugade, Deepali H.; Surushe, Aniket (International Journal of Advances in Medicine, 2018)
Retroperitoneal Lymphangiomas are rare and account for only 1% of lymphangiomas. They usually present in infancy, rarely they may present symptomatically in adulthood. We present a case of a 19-year old female with a symptomatic retroperitoneal lymphangioma. It was treated with complete surgical excision. Retroperitoneal lymphangiomas are rare. Imaging alone cannot differentiate them from other retroperitoneal cystic masses. Surgical excision is the treatment of choice and required for final diagnosis.